Music motivation depends on what to motivate: research review of Gumm’s music teaching and conducting models - Gumm, Alan J. (Frontiers in Psychology, 2023)
The history and philosophy of music education is traced with varied efforts to hone, enhance, and shift a strong tradition of performance-based instruction. The purpose of this paper is to summarize research of Gumm's empirical models that encapsulate eight music teaching and six conducting approaches and their use over the past 35 years toward varied philosophical aims. Each approach coordinates a distinct set of instructional and motivational behaviors toward a particular learning effect or outcome. Different balances of approaches reveal broader aims such as performance, comprehensive musicianship, cooperative, discovery, and affective learning, or even basic on-task behavior. Broader yet are two overarching aims found in common to both music teaching and conducting-to control or release. Controlling music teaching asserts correct on-task behavior through clear task directions and corrective feedback, motivates attention to task nonverbally, efficiently fills time with active tasks, and clarifies and affirms positive learning; whereas cooperative group leadership releases interdependent learning, questioning fosters music concept learning, imagery and movement release artistry, and discussing unique perspectives releases independent ideas and feelings. In conducting, precise gestures control accurate timing, signals and alerts motivate attention, and mimicry of musician exertions controls physical tone production; whereas shaping of phrases and score markings release musical expression, psychosocially familiarized gestures foster interdependence, and tension-easing gestures release freer independent tone production. Control-oriented teaching is most prevalent across the field, yet links to greater burnout and appeals to accommodating students motivated by effort and ability more than to students motivated by social and affective enjoyment of music. In conducting, music-oriented precision and expression are more prevalent than musician-oriented approaches. Releasing approaches are more 2 prevalent in Western than Eastern culture, upper levels, early rehearsals well before concerts, smaller ensembles, competitive ensembles, and teachers and conductors with greater experience or varied movement training. A key conclusion is that the choice of how to teach and conduct music effectively depends on the intended effect, the same as for the choice of how to motivate. Future research is suggested in general music and popular, jazz, folk, community, and professional music ensembles, as well as longitudinal career studies.